Transient rotation of photospheric vector magnetic fields associated with a solar flare - Yan Xu (Nature Portfolio, 2018)
The violent solar eruptions known as flares are caused by magnetic reconnection. Here, the authors identify a sudden 12°–20° counter clockwise rotation of vector magnetic fields in photosphere, associated with the emissions of moving flare ribbons.